The Palgrave International Handbook of Mixed Racial and Ethnic Classification 2020
DOI: 10.1007/978-3-030-22874-3_34
|View full text |Cite
|
Sign up to set email alerts
|

Multiracial in Malaysia: Categories, Classification, and Campur in Contemporary Everyday Life

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In our study, race, residency, smoking habit, alcohol consumption, sleeping quality, and BMI showed a significant association with anxiety. Malaysia is a multi-racial country with different cultures, beliefs, and social activities [25]. The association of different race and anxiety by several studies has been reported by Anderson & Mayes (2010) in their review.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 92%
“…In our study, race, residency, smoking habit, alcohol consumption, sleeping quality, and BMI showed a significant association with anxiety. Malaysia is a multi-racial country with different cultures, beliefs, and social activities [25]. The association of different race and anxiety by several studies has been reported by Anderson & Mayes (2010) in their review.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 92%
“…The syllabus also contains components that can strengthen racial unity and national harmony (Salleh and Khahar, 2016). Thus, the national education system has indirectly inculcated the values of peace and mutual respect between different ethnic communities (Reddy and Selvanathan, 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…How did the policies and issues have their impacts on people's ERI in different stages of their lifespan? Reddy & Selvanathan argues that "Non-Malays are driven to identify themselves with their racial groups to differentiate themselves from the 'default' identity" (Reddy & Selvanathan, 2020). According to Crouch (2001), as cited in Ethnic Identity and Other-Group Orientation of Ethnic Chinese in Malaysia by Ting & Ting (2020), "emphasis on the Malay culture as the basis of the national culture made "many non-Malays feel that they were no more than secondclass citizens".…”
Section: Application Of Eri Developmental Concepts In Malaysia Settin...mentioning
confidence: 99%